Emerging Anti-inflammatory Therapies for Atherosclerosis - Roubille, Francois; A. Kritikou, Ekaterini; Roubille, Camille; Tardif, Jean-Claude (Current Pharmaceutical Design, 2013)
Atherosclerosis remains one of the main causes of cardiovascular disease, which is the leading cause of death worldwide. It is now accepted that atherosclerosis is an inflammatory, dynamic and complex disease involving multiple cell types, and many antiinflammatory strategies have recently emerged as potential therapeutic approaches for atherosclerotic disease. In this review, we discuss the most recent progress in the development of anti-inflammatory strategies. We highlight the beneficial effects of potent antiinflammatory drugs, including recently developed biologics, and we describe diverse emerging approaches that target inflammatory processes involved in atherosclerosis including tumor necrosis factor antagonists, anti-interleukins, viral-derived serpins, P-selectin inhibition and leukotriene synthesis inhibition.
Keywords: P-selectin